Electrochemical Detection of Cadmium and Lead in Rice on Manganese dioxide Reinforced Carboxylated Graphene Oxide Nanofilm - Ali Osman Solak; Aslı Erkal; Zafer Üstündağ; İlknur Üstündağ (MANAS: Journal of Engineering, 2018)
Manganese dioxide decorated carboxylated grapheneoxide (Mn-GO-COOH) attached onto the glassy carbon (GC) electrode to develop anew method for the simultaneous determination of Cd2+ and Pb2+ions in rice samples. Graphene oxide (GO) was attached on 4-aminophenylcovalently modified glassy carbon surface via amide reaction. As-prepared modifiedmaterial was characterized with XPS, SEM and electrochemical methods. A noveldifferential pulse anodic stripping voltammetric (DPASV) method was developedfor the simultaneous determination of Cd2+ and Pb2+ onthe GC/Mn-GO-COOH nanoplatform electrode. A linear response was found for theheavy metals in the range from 5 to 100 mg/L. The limit of detections (LODs) of Cd2+ andPb2+ were 0.04 mg/L and 0.08 mg/L respectively. Manganese dioxide decoratedcarboxylated graphene oxide electrode was applied to the detection of Cd2+and Pb2+ present in different rice samples by developedvoltammetric method, and the accessed results were found to be in accordancewith that of ICP-OES.